Verification and validation of IM-DeCRuD approach using DESMET for its applicability - Jamaluddin Jasmis; Shamsul Jamel Elias; Azlan abdul Aziz; Mohd Zaki Zakaria; R Badlishah Ahmad; Roshidi Din; Rosmadi Bakar (Institute of Advanced Engineering and Science, 2019)
Requirements crosscutting in software development and maintenance have gradually become an important issue in software engineering with a growing need of traceability support to better understand the requirements crosscutting processes to comply with industrial standards. However, many recent works focusing on identification, modularization, composition and conflict dissolution of requirements crosscutting are mostly saturated at requirements level. Hence, these works fail to specify crosscutting properties for functional and non-functional requirements at other phases leading to insufficient support for software engineers. Recently, a new approach called the Identification, Modularization, Design Composition Rules and Conflict Dissolutions (IM-DeCRuD) was proposed to provide a special traceability to facilitate better understanding and reasoning towards requirements crosscutting implementation, along with a tool as a proof-of-concept. In this paper, the tool was evaluated and the results were verified by some experts in the industries. The feedbacks on applicability aspect were then gathered and analyzed using DESMET qualitative method. The outcome showed that the IM-DeCRuD was applicable to cope with the tedious engineering processes in handling crosscutting properties at requirements, analysis and design phases for system development and evolution.